QUALITY IMPROVEMENT OF FEED CHEMICAL COMPOSITION WITH THE ADDITION OF DRAGON FRUIT SKIN FLOUR (Hylocereus polyrhizus) - Tulas Aprilia; Rakhmawati Rakhmawati (University of Lampung, 2021)
Providing high-quality feed is one of the efforts to increase fish productivity and growth and reduce fish mortality. One of the additional alternative feed ingredients as a source of vegetable protein is dragon fruit peel which can be used as an additional ingredient in fish feed. The study of the chemical composition of feed with the addition of dragon fruit peel flour is essential information to determine the effect of addition and the benefits of by-products (waste) from food processing in aquaculture development. This study aims to evaluate the quality of the chemical composition of feed after being treated with the addition of dragon peel flour through proximate analysis. The test was carried out at the Agricultural Product Technology Laboratory of Lampung State Polytechnic, from June to August 2020. The test results showed that dragon fruit peel flour had a carbohydrate content of 50.74%, crude fiber 26.22%, ash 21.35%, protein 5.08%, and fat 4.80% (dry weight). The test results showed that the addition of dragon fruit peel flour increased the protein content in the feed, which increased with the increase in the added dragon fruit flour. The highest protein content in treatment was 1.5%, namely 37.79% (dry weight), and decreased in the addition of dragon fruit flour by 2.0%. The highest ash content in the addition of 2.0% was 11.32% (dry weight). The content of crude fiber, carbohydrates and fat has decreased with the increasing dose of dragon fruit flour. The addition of dragon fruit peel flour can increase the protein content in the feed to substitute in the manufacture of fish feed. This also increases the utilization of dragon fruit peel waste, especially in aquaculture, to reduce waste disposal into the environment.